KASBIY KOMPETENSIYANI RIVOJLANTIRISHDA KASBIY-PEDAGOGIK TA’LIMNI UYG‘UNLASHTIRISH ASOSLARI - Jumasheva, G.X.; Erimbetova, P.R. (SCIENCE and SOCIETY, 2024)
The article is devoted to the problem of the principles of harmonizing professional-pedagogical education in the development of professional competence. In the article, the new content of the development of the professional competence of pedagogic personnel in the educational organization is told about the need for continuity and the foundations of the innovative direction in the training of specialists of the educational organization for the new society.
Keywords: development of professional competence; professional-pedagogical education; pedagogical staff; new content; new society; educational organization; training of specialists; innovative direction